Determinants of Inbound Tourism Revenues in Peru: Evidence from a Crisis Period - Enriquez-Perales, Sarela; Garcia-Gomez, Conrado Diego; Bolanos, Edmundo R Lizarzaburu (Journal of Tourism Management Research, 2022)
The strand of the tourism literature focusing on emerging markets is relatively scarce. However, the increasing importance of tourism activity in emerging economies in the last years is moving the academic attention to countries like Peru, where tourism activity has become an essential part of its recent economic development. Accordingly, this paper analyzes the determinants of tourism demand in Peru, by estimating a single-equation model for the period 2007-2011. Specifically, it is proposed as a tool to analyze and understand the recent evolution of this industry as the basis for growth in the Andean country. The obtained results confirm the positive relationship between the real income of non-resident tourists and tourism demand, while tourism in Peru is not eligible as a luxury good. Additionally, it is shown that there is not a high sensitivity of real income from tourism to inflation differentials. The obtained results provide important implications for policymakers. Namely, it becomes relevant to better understand a country’s tourism demand determinants in order to consolidate its economic contribution in times of economic recession.